Teriparatide Therapy Enhances Devitalized Femoral Allograft Osseointegration and Biomechanics in a Murine Model - Reynolds, David G. (2010)
Despite the remarkable healing potential of long bone fractures, traumatic injuries that result in critical defects require challenging reconstructive limb sparing surgery. While devitalized allografts are the gold standard for these procedures, they are prone to failure due to their limited osseointegration with the host. Thus, the quest for adjuvants to enhance allograft healing remains a priority for this unmet clinical need. To address this, we investigated the effects of daily systemic injections of 40 µg/kg teriparatide (recombinant human parathyroid hormone) on the healing of devitalized allografts used to reconstruct critical femoral defects (4 mm) in C57Bl/6 mice. The femurs were evaluated at 4 and 6 weeks using micro CT, histology, and torsion testing. Our findings demonstrated that teriparatide induced prolonged cartilage formation at the graft-host junction at 4 weeks, which led to enhanced trabeculated bone callus formation and remarkable graft-host integration at 6-weeks. Moreover, we observed a significant 2-fold increase in normalized callus volume (1.04 ± 0.3 vs. 0.54 ± 0.14 mm(3)/mm; p<0.005), and Union Ratio (0.28 ± 0.07 vs. 0.13 ± 0.09; p<0.005), compared to saline treated controls at 6-weeks. Teriparatide treatment significantly increased the torsional rigidity (585±408 versus 1175±311 N.mm(2)) and yield torque (6.8±5.5 versus 10.5±4.2 N.mm) compared to controls. Interestingly, the Union Ratio correlated significantly with the yield torque and torsional rigidity (R(2)=0.59 and R(2)=0.77, p<0.001, respectively). These results illustrate the remarkable potential of teriparatide as an adjuvant therapy for allograft repair in a mouse model of massive femoral defect reconstruction, and warrant further investigation in a larger animal model at longer time intervals to justify future clinical trials for PTH therapy in limb sparing reconstructive procedures.